Persistency and permanency of two stages splicing languages based on DNA recombination process by using Yusof-Goode (Y-G) approach - Mohammad Hassan, Mudaber (2015)
The study of the biological process of deoxyribonucleic acid (DNA) splicing was investigated by Yusof in 2012 as a translucent approach under framework of formal languages theory. The investigation was achieved by proposing a new symbolization representing the rule in splicing system called Yusof-Goode (Y-G) rule associated with Y-G splicing system. A laboratory experiment is usually performed to show the DNA splicing process under the existence of restriction enzyme and appropriate ligase. This laboratory experiment is time consuming process and it can incur a lot of expenses. In addition, to accomplish the reaction up to two stages the generating recombining DNA molecules must have persistency concept. Thus, to overcome this problem, mathematical approach via Y-G model is applied to introduce the new concept of splicing system at two stages with respect to two initial strings and two rules. Furthermore, the existence relation between the families of stage one and stage two splicing languages are investigated. In this investigation, some sufficient conditions for persistency and permanency of two stages DNA splicing languages according to the number of cutting sites of initial strings and properties of rules are provided. The de Bruijn graph is used to predict the persistency and permanency of two stages splicing languages. A user friendly interface as an alternative of wet-lab experiment is coded using Microsoft Visual C Sharp (C#) to predict the persistency and permanency, and the relations between two stages (stage one and stage two) splicing languages.